Factors influencing parental decisions to terminate pregnancies following prenatal diagnoses of major fetal anomalies at Ramathibodi Hospital, Bangkok, Thailand - Papapin Pusayapaibul; Jittima Manonai; Chayada Tangshewinsirikul (BMC, 2022)
Abstract Background The rate of termination of pregnancy (TOP) for fetal anomalies and the factors affecting TOP vary among different populations. Optimisation of prenatal care and counselling requires understanding the factors influencing parental decisions in the relevant population. This study aimed to evaluate the rate of TOP after diagnoses of major fetal anomalies and assess factors associated with TOP-related decisions at a university hospital in Thailand. Methods A retrospective chart review was conducted at the Fetal Anomaly Clinic of Ramathibodi Hospital, Bangkok, Thailand. Medical records of all women with singleton pregnancies prenatally diagnosed with major fetal anomalies before 24 gestational weeks between 2010 and 2020 were reviewed. Results During the study period, 461 cases of major fetal anomalies were diagnosed, and 264 (57.3%) of these pregnancies were terminated. Three factors influencing parental TOP decisions were lethal anomalies (odds ratio [OR], 197.39; 95% confidence interval [CI], 49.95-779.95; p < 0.001), presence of genetic abnormalities (OR, 10.19; 95% CI, 4.17-24.87; p < 0.001) and gestational age at diagnosis (OR, 0.74; 95% CI, 0.65-0.84; p < 0.001). Conclusions Over half of the pregnant women whose records were reviewed and who were prenatally diagnosed with major fetal anomalies terminated their pregnancies. Fetal factors, particularly lethality, genetic abnormalities and early gestational age at diagnosis, showed the most powerful associations with parental TOP decisions. Other maternal background factors were not key considerations.